GREAT SCHOLARS OF IX-XII CENTURIES INMOVAROUNNAHR AND KHORASAN - Teshaboyeva Nafisa Zubaydulla qizi; Abduvahobova Sevara Sobirjon qizi (TADQIQOTLAR.UZ, 2024)
Abstract:Great Scholars of the 9th-12th Centuries in Greater Khorasan.The region of Greater Khorasan, which umfasst the modern-day countries of Iran, Afghanistan, Uzbekistan, Tajikistan, and Turkmenistan, was a major center of learning and scholarship during the 9th-12th centuries. This period saw the flourishing of many great scholars in a wide range of fields, including philosophy, science, mathematics, and medicine. The work of these great scholars helped to lay the foundation for the scientific and intellectual revolution that took place in Europe during the Renaissance and Enlightenment periods. Their work continues to be studied and admired today, and they remain an inspiration to scholars and students around the world.